2006
DOI: 10.1002/crat.200610774
|View full text |Cite
|
Sign up to set email alerts
|

XRD, thermal, FTIR and SEM studies on gel grown γ‐glycine crystals

Abstract: Glycine is the smallest among amino acids. The polymorphs, α-and γ-forms of glycine were crystallized in silica gel by reduction of solubility method. The grown crystals were characterized by single crystal X-ray diffraction studies and density determination. Fourier transform infrared spectroscopic studies and thermogravimetric analysis of γ-glycine were also conducted. Morphological and scanning electron microscopic (SEM) studies were also made and compared with the crystal packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…But in other amino acids without additional OH molecules, carbon monoxide may be released instead of CO 2 . The chemical reaction expected to occur during decomposition of L-valine will be as in the case of γ-glycine explained elsewhere [22].…”
Section: Resultsmentioning
confidence: 98%
“…But in other amino acids without additional OH molecules, carbon monoxide may be released instead of CO 2 . The chemical reaction expected to occur during decomposition of L-valine will be as in the case of γ-glycine explained elsewhere [22].…”
Section: Resultsmentioning
confidence: 98%
“…The absorption at 3457.2 cm −1 is attributed to the stretching of O−H group, indicating the presence of water of crystallization or water of hydration [20]. The absorption at 1575.7 cm −1 is assigned to C=O stretching of carbonyl group [21]. Sheveheko [22] suggested that the IR spectra of both normal and partrially deutereted compounds of some tartrates exhibit absorption from 600 cm −1 to 400 cm −1 due to COO − group in metals and suggested the formula as shown in figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…In the spectra of CH-BNT and AZ-BNT, the absorption bands at 3626 and 3640 cm‾ 1 indicate the presence of free O-H stretching and at 1091 and 1109 cm‾ 1 correspound to C-N stretching [19,20]. In addition to the bands of the original Na-BNT, the band at 1490 and 1438 cm‾ 1 suggests the existence of the ammonium ion.…”
Section: Ftir Spectroscopymentioning
confidence: 99%